Incidence of Carboplatin-Related Hypersensitivity Reactions in Japanese Patients With Gynecologic Malignancies. Issue 3 (1st March 2009) - Koshiba, H.; Hosokawa, K.; Kubo, A.; Miyagi, Y.; Oda, T.; Miyagi, Y.; Watanabe, A.; Honjo, H.
Abstract : Carboplatin is one of the most commonly used and well-tolerated agents for gynecologic malignancies. The rate of hypersensitivity reactions (HSRs) in the overall population of patients receiving carboplatin has been reported to increase after multiple doses of the agent. We retrospectively analyzed the incidence, clinical features, management, or outcome of carboplatin-related HSRs in 113 Japanese patients with gynecologic malignancies and the possibility of rechallenge with the drug. We intravenously administered carboplatin after paclitaxel or docetaxel. Mild HSRs are resolved by temporary interruption of carboplatin infusion, an additional antihistamine, and/or a corticosteroid. If HSRs arose, carboplatin was diluted, not exceeding 1 mg/mL, and slowly infused over 2 hours in subsequent cycles. Ten patients experienced carboplatin HSRs, with an overall incidence of 8.85%. The first HSR episode was mild in all cases. When retreated with carboplatin, 4 exhibited severe HSRs. More than 9 cycles and/or more than 5000 mg of carboplatin administration significantly increased the incidence of HSRs. In particular, carboplatin treatment beyond 15 cycles and/or 8000 mg increased the risk of severe HSRs ( P < 0.0001). The incidence of HSRs in the ovarian carcinoma group was significantly greater than that in the uterine carcinoma group ( P = 0.0046). Careful attention should be paid to HSRs during carboplatin treatment beyond 9 cycles and/or 5000 mg. The rate of severe HSRs greatly increases beyond 15 cycles and/or 8000 mg. Further studies are needed to identify potential risk factors that may contribute to the development of carboplatin HSRs and to decrease the risk of reactions.